Fundamental principles of data assimilation underlying the Verdandi library: applications to biophysical model personalization within euHeart. - Chapelle, D; Fragu, M; Mallet, V; Moireau, P (Medical & Biological Engineering & Computing, 2013)
We present the fundamental principles of data assimilation underlying the Verdandi library, and how they are articulated with the modular architecture of the library. This translates--in particular--into the definition of standardized interfaces through which the data assimilation library interoperates with the model simulation software and the so-called observation manager. We also survey various examples of data assimilation applied to the personalization of biophysical models, in particular, for cardiac modeling applications within the euHeart European project. This illustrates the power of data assimilation concepts in such novel applications, with tremendous potential in clinical diagnosis assistance.